Manufacturing hands: robot fingers and human labour in post-war Japan. (3rd July 2022) - Frumer, Yulia
ABSTRACT: This article argues that automation engineering in 1960s Japan was rooted in colonial attitudes towards human labour, which were tacitly present in Japan even decades after its defeat in World War II. I make this argument by examining the development of Japan's first modern robot, a three-fingered mechanical hand designed by Tokyo University graduate student Yamashita Tadashi in 1963. Exploring Yamashita's methods, the data he relied on, and the literature he drew inspiration from reveals that his design was modelled on human hands. Yamashita and his contemporaries were influenced by colonial assumptions about labour. Specifically, they accepted a tacit division of workers into two kinds: the engaged and cherished Japanese citizen; and the hardy, silent, colonial subject to whom fell the most dangerous and undesirable work. As Yamashita worked to make an autonomous and versatile robot, he recast its image as an engaged and cherished worker, paving the way for the Japanese reconceptualization of robots as friends. Retracing Yamashita's process of making a robotic hand thus reveals that the automation of labour is predicated on the perceptions of humans whose labour robots are intended to replace.